Функционална двокодност међу студентском популацијом - Miketić Subotić, Sanja D. (Collection of Papers of the Faculty of Philosophy in Priština, 2017)
The aim of this paper is to present attitudes towards the usage of native dialect and standard language among students, and to establish if certain sociodemographic variables may affect further differences in the answers of the survey participants. Variables observed in this research are: students’ gender, university they attend (University of Priština, with temporary head office in Kosovska Mitrovica or University of Belgrade), their study field (if they are students of Serbian language or non-linguists), place they live (town, suburban area or village), and their native dialect. This quantitative study was conducted with 240 participants (60 of whom are students of Serbian language at the University of Belgrade (BU) and 60 students of Serbian language at the University of Priština, with temporary head office in Kosovska Mitrovica (UPKM); 60 are students of natural sciences at BU and 60 at UPKM). The hypothesis we wanted to verify is that the domain of native dialect usage is mostly for the private conversation, while the standard language usage is usually connected with official situations; in addition, students have a highly developed awareness of using each variety depending on the situational context.